Meta-Analysis of the Effect of Policy Lockdown on Anxiety in Adults - Rohmah, Isna Nur; Sekar, Fauzia Ichlasul; Samudera, Galang Aji; Anasulfalah, Hakim; Ningsih, Hepti Widia; Paramastri, Izdihar Azzah; Wijayanto, Masromi Hendria; Arianty, Meike; Putra, Muhammad Dudayev Caesar; Husein, Muhammad Fajar (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2021)
Background: On March 11, 2020, the World Health Organization (WHO) has declared an outbreak of a new coronavirus (COVID-19) as a global pandemic. In responding to the threat of the COVID-19 virus pandemic, policymakers have implemented a policy lockdown that can cause psychological distress, one of which is anxiety. This study aims to examine the effect of the policy lockdown on anxiety in adults using a meta-analysis.Subjects and Method: Meta-analysis was performed by searching for articles from the database, namely PubMed, Google Scholar, Science Direct, Scopus, and Crossref. The keywords used are